'Just checking': Vulnerable and grandiose narcissism subtypes as predictors of phubbing. (May 2021) - Grieve, Rachel; March, Evita
"Phubbing" (phone snubbing) refers to a set of behaviors where phone users focus on their mobile phone instead of interacting with their physically proximal companions. Building on existing understanding of problematic phone use, this study examined narcissism subtypes as predictors of phubbing behavior. Participants ( n = 250 smartphone users) completed an anonymous online study where they reported their phubbing behaviors and completed measures of vulnerable narcissism, grandiose narcissism, psychopathy, and Machiavellianism. Analysis was via multiple regression, with vulnerable and grandiose narcissism as predictors; psychopathy and Machiavellianism were also included to account for shared variance with grandiose narcissism. As hypothesized, vulnerable narcissism emerged as a significant predictor in the model, such that higher levels of vulnerable narcissism were associated with more phubbing. In light of previously established negative social outcomes associated with phubbing behaviors, we conclude that although phubbing might help those high in vulnerable narcissism to manage their need for admiration and their contingent self-worth, phubbing may be particularly problematic for these individuals.